Design Packaging Box Product Compact Disc Type Training for High School Graduate and Equivalent in Tangerang - Ali Ramadhan; Djoko Soemarsono (Institute for Research and Community Services, 2017)
Packaging is known as product protection and can provide an identity to the product. Box packaging has been known as one of the packaging types that is able to provide security to the product. Currently, compact discs are products that still require packaging that can help in providing an identity. Through training that can provide knowledge and expertise in packaging box design, it is hoped that the community, especially high school graduates and their equivalents, may have new experience and understanding with respect to packaging design process that can be utilized for industrial purposes, especially those related with packaging design. Packaging design for compact discs can help provide an identity which distinguishes one compact disc product from another in the market.